National Ecological Network: Problems of Controlled Development - G. G. Baranets (Наука и техника)
The necessity to elaborate the Principal Scheme of National Ecological Network (PSNEN) has been caused by new requirements of the national policy in the field of environmental protection. The main purpose of PSNEN elaboration is to develop methodological basis for the next planning cycle in order to develop the system of especially protected nature territories. Such planning is executed in accordance with requirements of National Legislation in the field of especially protected nature territories. Peculiar feature of the proposed methodology consists in the interrelated consideration of urban framework, on the one side, and ecological network, on the other one, as two basic components of the spatial Republican framework..